Development of PBL-Based Math Comics for the Improvement of Students’ Critical Thinking Skills - Reni Yannur; Jefri Marzal; Ilham Falani (MASI Mandiri Edukasi, 2026)
The development of Problem-Based Learning (PBL)-based mathematics comics involves creating mathematics learning media that combine elements of pictures and stories to help students understand concepts and improve their critical thinking skills. The development of PBL-based math comics uses the Canva and Live Worksheets applications. This research aims to produce PBL-based math comic worksheets for students, created in Canva and Live Worksheets, to improve critical thinking skills in Phase D students. The research carried out is Research and Development (R&D), using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The results of the research are PBL-based math comic worksheets to improve students' critical thinking skills, accessible on various internet-connected devices. This math comic worksheet focuses on the Pythagorean Theorem for Phase D students, presenting problems in a context-based format and using easy-to-understand language. The research was conducted at SMP IT Nurul 'Ilmi 2 Jambi City with one mathematics teacher, nine students in the small group trial, and 28 students in the large group trial. The results of the study show that the product developed underwent several revisions to become worthy of testing. The instrument used uses the Guttman scale, so that the final validation after revision reaches 100%. The validity of PBL-based math comic worksheets is 100% (very valid) according to material experts and 100% according to media design experts. The percentage of practicality of PBL-based math comic worksheets by educators is 100% (very practical), and by students is 98% (very practical), and the percentage of effectiveness of PBL-based math comic worksheets from the student response questionnaire is 98% (effective). The learning outcome test, in the form of a pre-test and post-test using N-Gain, was completed by 16 people in the medium category, 10 in the high category, and 2 in the low category.